Identifying Gaps in Predoctoral Craniofacial Education - Catherine Bingham; Linda Sangalli; Kathryn Preston; Poojan Shrestha; Caroline M. Sawicki (Dentistry Journal)
Background/Objectives: It is essential that dental school graduates are adequately prepared to provide care to patients with craniofacial differences (PCD). This study aimed to identify potential educational deficiencies in predoctoral dental school curricula regarding the management of PCD. Methods: An electronic survey was distributed to predoctoral dental students across the United States. The 20-item questionnaire assessed students’ educational experiences, clinical encounters, and perceived knowledge and confidence in managing PCD. Results: The most taught didactic topic was diagnostic characteristics of craniofacial differences (77.1%), followed by psychosocial challenges (43.0%) and treatment/referral (36.3%). Respondents reported low levels of understanding and confidence in managing craniofacial conditions, with the lowest confidence in providing surgical treatment (30.1 ± 27.9) and the highest in referrals and communication (41.7 ± 30.1, on a 0–100 scale). Logistic regression showed that overall understanding was a significant predictor of confidence, increasing odds by 8% (OR = 1.08, 95% CI 1.05, 1.12). Participants noted that hands-on clinical experience would most improve their confidence in managing PCD. Conclusions: Predoctoral dental students exhibit low confidence and understanding in managing PCD. Incorporating more targeted craniofacial education, particularly hands-on clinical experience, into the curriculum is essential to better prepare dental graduates for craniofacial care.